Analysis of Decision Making to Add Fixed Assets to CV. Esamanta - Marcia Judith Kopalit; Treesje Runtu; Natalia Y. T. Gerungai (Formosa Journal of Applied Sciences, 2023)
Decision making is an important element in a company because it concerns what will be faced in the future. Activities to buy or rent fixed assets are carried out to expand the business sector so that consumer demand can be met optimally. The aim of this research is to analyze appropriate decision-making alternatives to be made to add fixed assets to CV. Esamanta. This research uses a descriptive research method with a qualitative approach by analyzing the facts that occur and the theories or regulations applied in the field. The research results show that CV. It is more profitable for Esamanta to choose the alternative of renting a vehicle compared to buying a vehicle. By renting a vehicle, the company can save costs of IDR. 44,609,850 in 2024 – 2028 or over the useful life of the vehicle according to company policy, which is 5 years.